Kłodzko Fortress – as an integral element of the city structure - Gleń, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
This article presents the importance of a historical element in the city structure which is the Kłodzko Fortress. This towering military building is an important dominant located in the center of Kłodzko. The author citing the analyzes and research carried out by him in the territory of the Twierdza, bringing closer the possibilities of using the adaptive potential of this place. This object, once performing a signifi cant military function, should now have a completely new application. Also presenting the examples of adaptation of this type of objects from the country and the world, the cultural and economic potential for the region has been presented. Objects that do not fulfi ll their target function fall into ruin, losing values and potential hidden in them. The adaptive possibilities of the Kłodzko Fortress allow for the introduction of various functions to it, which may result in an enrichment of its value. Giving a contemporary function in a facility located in the center of the Kłodzko valley is to have an added element, i.e. a synergy effect for the city and the area in which it is located. Based on the materials developed by the author, the potential of the place is presented as an attractive commercial and cultural object. Presenting adaptation methods, at the same time, attention is paid to the risks associated with leaving the Fortress to destructive activities.